Decreased SGK1 Expression and Function Contributes to Behavioral Deficits Induced by Traumatic Stress - Licznerski, Pawel; Duric, Vanja; Banasr, Mounira; Alavian, Kambiz N.; Ota, Kristie T.; Kang, Hyo Jung; Jonas, Elizabeth A.; Ursano, Robert; Krystal, John H.; Duman, Ronald S. (PLoS biology, 2015)
Exposure to extreme stress can trigger the development of major depressive disorder (MDD) as well as post-traumatic stress disorder (PTSD). The molecular mechanisms underlying the structural and functional alterations within corticolimbic brain regions, including the prefrontal cortex (PFC) and amygdala of individuals subjected to traumatic stress, remain unknown. In this study, we show that serum and glucocorticoid regulated kinase 1 (SGK1) expression is down-regulated in the postmortem PFC of PTSD subjects. Furthermore, we demonstrate that inhibition of SGK1 in the rat medial PFC results in helplessness- and anhedonic-like behaviors in rodent models. These behavioral changes are accompanied by abnormal dendritic spine morphology and synaptic dysfunction. Together, the results are consistent with the possibility that altered SGK1 signaling contributes to the behavioral and morphological phenotypes associated with traumatic stress pathophysiology.